BENTUK PERTUNJUKAN TARI SERABI KALIBELUK DI SANGGAR JAGADHITA KABUPATEN BATANG - Oktoviany, Fillaily; Kusumastuti, Eny (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study discusses the performance form of the Serabi Kalibeluk Dance as a creative dance work based on local culture, developed at the Jagadhita Studio in Batang Regency. The problem addressed in this study is how the Serabi Kalibeluk Dance is performed at the Jagadhita Studio in Batang Regency. The purpose of this study is to explore and describe in detail the performance form of the Serabi Kalibeluk Dance, including the supporting elements of the performance such as the dance movements, presentation structure, and visual components involving music, costumes, and props. This research employs a qualitative approach with an ethnocoreological method and Jazuli's theory, using data collection techniques such as observation, interviews, and documentation. The data collected was analyzed through data reduction, data presentation, and verification techniques. The findings reveal that the Serabi Kalibeluk Dance not only reflects the cultural character of Batang but also serves as an educational medium that represents the historical, social, and traditional values of the local community. The performance form of this dance holds high aesthetic value and plays an important role in the preservation of regional arts. The conclusion emphasizes that the Serabi Kalibeluk Dance is an expression of local culture, containing educational and aesthetic values, and is essential in the efforts to preserve traditional art forms.